1974
DOI: 10.1029/jb079i017p02679
|View full text |Cite
|
Sign up to set email alerts
|

A velocity anomaly in the lower mantle

Abstract: A study of ScS-S and PcP-P differential travel times and absolute S wave travel times from two deep focus South American earthquakes indicates that the scatter observed in ScS-S times by Hales and Roberts (1970) and Jordan (1972) results from lateral heterogeneities in the lower mantle along the path of the S phase. Both ScS-S and PcP-P times delineate a region of anomalously high velocity in the lower mantle beneath the Caribbean, which may be responsible for some observations of body wave multipathing at Las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(42 citation statements)
references
References 6 publications
(1 reference statement)
4
38
0
Order By: Relevance
“…Jordan and Lynn, 1974]. However, from resolution analyses it can not unambiguously be concluded that the high velocity feature is continuous across the transition zone to the site where presently the Cocos Plate subducts beneath Middle America.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Jordan and Lynn, 1974]. However, from resolution analyses it can not unambiguously be concluded that the high velocity feature is continuous across the transition zone to the site where presently the Cocos Plate subducts beneath Middle America.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The lower mantle structure may tentatively be interpreted as the image of the subducted Farallon Plate [e.g. Jordan and Lynn, 1974;Grand, 1987]. If so, the broadening of the slab below the transition zone may also be explained by advective thickening due to the increase in viscosity [Fischer and Jordan, 19881.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Another section through the EPR shows low mantle velocities to a depth of 1300 km to the west of this structure. The reader may notice the elements of the "Pangea Trough," with the cross section showing the fast mantle under Canada and the "Caribbean anomaly" [Jordan and Lynn, 1974;Grand, 1987; van der Hilst and Engdahl,…”
Section: Scale Of Heterogeneity and Mantle Dynamicsmentioning
confidence: 99%
“…As early as 1974, Jordan and Lynn (14) had identified anomalously high P and S velocities in the lower mantle beneath the Caribbean. Although P tomographic studies have poorest resolution on the lowermost mantle because of limited sampling, S-wave studies clearly show fast broad anomalies in the lowermost 500 km of the mantle beneath Central America (e.g., ref.…”
mentioning
confidence: 99%